Minat Beli Followers terhadap Produk UMKM: (Studi pada Akun Instagram @dinacarlaa) - Aminah Miliani; Noerma Kurnia Fajarwati; Meiby Zulfikar; Achmad Nashrudin Priatna; Putri Handayani (Badan Penerbit STIEPARI Press, 2025)
The development of digital technology and the increasing use of social media, especially Instagram, provide significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) in marketing their products. The Instagram account @dinacarlaa is one example of an account that actively promotes MSME products through visual content, reviews, and customer testimonials. This study aims to analyze followers' purchasing interest in MSME products promoted through the account. The study used a quantitative approach with a positivistic paradigm, with a population of 33.4 thousand followers of the @dinacarlaa account. The sample was determined using the Slovin formula with a 10% error rate, resulting in 100 active respondents. Data were collected through an online questionnaire with a Likert scale, then analyzed using simple linear regression. The results showed a significant influence of the @dinacarlaa Instagram account on followers' purchasing interest, with a regression coefficient of 0.698 and a significance level of 0.000 (<0.05). The coefficient of determination (R²) of 0.583 indicates that 58.3% of the variation in followers' purchasing interest is influenced by the account's content, while the remainder is determined by external factors. Descriptively, the majority of respondents indicated high purchasing interest, with 88% having purchased a product after seeing a promotion, and 87% learning about MSME products from accounts' posts. These results confirm that post consistency, visual quality, and influencer credibility are crucial in shaping consumer purchasing interest and strengthening MSMEs' digital marketing strategies.